Abnormal Psychology / DSM-5 Updated: Twelfth Edition - Davison Gerald C; Johnson, Sheri L.; Kring, Ann M.; Neale John M (John Wiley & Sons, Ltd, 2014)
The first and foremost grounded in the latest science of mental illness. Introduction and Fundamental Issues, Introduction and Historical Overview, Current Paradigms in Psychopathology, Diagnosis and Assessment, Research Methods in Psychopathology, Psychological Disorders, Mood Disorders, Anxiety Disorders, Obsessive-Compulsive-Related and Trauma-Related Disorders, Dissociative Disorders and Somatic Symptom-Related Disorders, Schizophrenia, Substance Use Disorders, Eating Disorders, Sexual Disorders, Disorders of Childhood, Late life and Neurocognitive Disorders, Personality Disorders, Legal and Ethical Issues, Glossary, References, Name and Subject Index.